Debonding on command of adhesive joints for the automotive industry. (June 2015) - Banea, M.D.; da Silva, L.F.M.; Carbas, R.J.C.
Abstract: In this study a methodology to assure easy debonding of adhesive joints by combining the inductive heating method and the use of thermally expandable particles (TEPs) was developed. Two commercially structural adhesive systems used in the automotive industry (one polyurethane and one epoxy) were tested. First, the influence of TEPs content on the lap-shear strength of the TEPs-modified single lap joints was investigated. Further, the ability of the TEPs-modified joints to support temperature controlled debonding was evaluated. It was showed that the control of the debonding process by temperature is possible. The temperature needed for debonding is a function of TEPs content and can be lowered by increasing the TEPs content.